Magnetic field reduction principles and options of primary overhead distribution lines - Ibrahim I.R.; Farag A.; Said I.; Hussain H.; Rahman N.A. (2023)
Variables that affect the magnitude of the magnetic fields in distribution line system are the magnitude of the distribution lines' phase currents, the distance of the distribution lines from the observation points, the conductors' configurations, and the ground currents due to unbalanced phase current. By using the delta type and the horizontal type of 33 kV primary overhead distribution poles as models, this paper presents the case studies of the effect of that variables to the primary overhead distribution lines and proposes the design options such as increasing the height of the distribution lines, increasing the lateral distance from the distribution lines, compacting the lines conductors' spacing, minimizing the ground current by balancing the lines' phase currents, and optimizing phasing arrangement. Another design criteria such as cost, safety, reliability, system stability, etc. also need to be considered before the design options recommended can be applied 2005 IEEE.